Kadar air, Kadar protein, dan Kadar Serat Pangan pada Cookies dengan Substitusi Tepung Ubi Jalar Ungu dan Tepung Rebung - Nafira Alifianita; Aan Sofyan (Universitas Muhammadiyah Semarang, 2022)
Cookies are one of the snacks that can be used as an alternative in fulfilling high-calorie and protein foods. Cookies are a type of small oven biscuit made from wheat flour with the addition of fat, sugar, etc. This study aims to determine the water content, protein content and dietary fiber content of cookies with the substitution of purple sweet potato flour and flour. bamboo shoots. This experimental study used a completely randomized design (CRD), with purple sweet potato flour substitution treatment of 40%, 35%, 30% and 25%, which was combined with bamboo shoot flour at 0%, 5%, 10%, and 15 respectively. %. The results showed the lowest water content in F1 was 6.73%, the highest water content in F4 was 7.65%. The highest protein content in F4 was 5.20%, the lowest protein content in F1 was 3.62%. The highest dietary fiber content in F1 was 5.01% and the lowest dietary fiber content in F4 was 3.32%. There is a significant effect of each treatment on cookies.